Computational studies: A passive strategy to improve visual comfort by optimizing daylight uniformity in the classroom - Irnawaty Idrus; Sahabuddin Latif (ARTEKS : Jurnal Teknik Arsitektur)
Even distribution of natural light is crucial in creating optimal visual comfort in classrooms. Many classrooms in tropical areas experience lighting imbalances, with areas near windows receiving excessive light, while others lack lighting. This study aims to evaluate the effectiveness of passive design strategies in improving the uniformity of natural lighting through a computational simulation approach. The research subjects include elementary, junior high, and senior high school classrooms in Makassar City, South Sulawesi. Modeling was conducted using Ecotect Analysis 2010 software, comparing two types of spaces: existing models and models with passive design interventions such as reflective floors. Simulation results show that passive design can improve daylight uniformity and significantly reduce glare potential. In addition to supporting visual comfort, the application of this strategy also contributes to energy efficiency by reducing dependence on artificial lighting. This study recommends the application of passive design as an integral part of sustainable classroom planning, especially in tropical climates.